Recent advances on yield stress and elasticity of fresh cement-based materials. (October 2019) - Roussel, N.; Bessaies-Bey, H.; Kawashima, S.; Marchon, D.; Vasilic, K.; Wolfs, R.
Abstract: The interest in the elastic and yielding properties of fresh cement-based materials has recently grown due to the development of new processing techniques, which avoid the use of standard formworks. Without support, the material shaping relies only on the mechanical properties of the fresh material. Within this frame, the point of this paper is to gather the accepted knowledge along with the most recent advances on both yield stress and elasticity of fresh cement-based materials. In the first part, we will go through the physical and chemical origin of these macroscopic properties and their evolutions. In the second part, we will describe the way they can be measured while the third part will deal with the way they can be controlled and tuned. Finally, the most recent models for both properties prediction from mix design and processing modeling from rheological measurements will be described.